Pengaruh Karakteristik Perusahaan terhadap Konservatisme Akuntansi Perusahaan Sektor Kesehatan yang Terdaftar di BEI Tahun 2019-2022 - Alfiyatush Nurul Jannah; Eni Wuryani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study was to determine and analyze the influence of company characteristics on accounting conservatism. The population of this study was 31 Health Companies for the period 2019-2022 listed on the Indonesia Stock Exchange. The independent variables used in this study consist of company size (LN), leverage (DER), liquidity (CR), and profitability (ROE), while the dependent variable is accounting conservatism (CONACC). The number of samples used as many as 60 samples with purposive sampling technique. This type of research is quantitative. Pengolaha research data using SPSS version 29 with multiple linear regression analysis method. Based on the results of the analysis that has been done, it is obtained that the size of the company, leverage, and liquidity have no effect on accounting conservatism, while profitability has an effect on accounting conservatism.